Gynecologic Cancer InterGroup (GCIG) Consensus Review for Ovarian Sex Cord Stromal Tumors. (1st November 2014) - Ray-Coquard, Isabelle; Brown, Jubilee; Harter, Philipp; Provencher, Diane M.; Fong, Peter C.; Maenpaa, Johanna; Ledermann, Jonathan A.; Emons, Gunter; Rigaud, Dominique Berton; Glasspool, Rosalind M.; Mezzanzanica, Delia; Colombo, Nicoletta
Abstract : Sex cord stromal tumors (SCST) are rare cancers of the ovarian area in adults. They constitute a heterogeneous group of tumors that develop from the sex cords and the ovarian stroma. These tumors are detected typically at an early stage, and they may recur as late as 30 years after the initial treatment. Because 70% of the patients present with stage I tumors, surgery represents the most important therapeutic arm. There are no data to support any kind of postoperative adjuvant treatment for patients with stage IA or IB SCSTs, given the indolent nature of these neoplasms and the overall good prognosis. The long natural history of the disease may lead to repeated surgical procedure should a relapse occurs. Platinum-based chemotherapy is currently used for patients with advanced stage SCSTs or recurrent disease, with an overall response rate of 63% to 80%. The indolent nature of SCSTs with the tendency for late recurrence requires long-term follow-up.